Literasi Budaya dan Budaya Lokal (Sebuah Upaya Perpustakaan Melindungi Sejarah Lokal) - Kardi Kardi (Pustakaloka, 2013)
It is ironic when reog Ponorogo (traditional art) was claimed by outsider (Malaysia) be a public attention especially, and Indonesian people generally. But the more ironic when Ponorogo didn’t have a study center about reog Ponorogo particularly and history and culture of Ponorogo generally. Library of STAIN Ponorogo as a preserver of history and culture had a significaant role to do it. Ponorogo corner service in it will be a service to respond information about Ponorogo, and it would be potential and distinctive service than any other services on other libraries.